Correlates of barangay high school performance - Salva, Teresita Lardizabal (1983)
The research focused on factors which can predict school performance (as measured by NCEE scores, percentage of graduates who pursue collegiate education, student involvement in livelihood projects, students' length of residence in the school, survival rate, percentage of graduates gainfully employed and students' work attitudes). The respondents consisted of 25 barangay high school principals, 131 teachers, 555 students and 500 community residents from Puerto Princesa City and Palawan province. School performance is associated with teacher-, administrator-, student-, school-, and community-related factors. The best predictors are the teacher variables (place of birth, length of residence in the barangay, mean age, and teacher commitment) and school variables such as school size, distance from the nearest high school, number of academic electives to the barangay.
Thesis (D.Ed.)--University of the Philippines, Diliman.
Keywords: Rural school -- Philippines -- Palawan